Kelimpahan dan Keanekaragaman Plankton di Bendungan Sinyur Jamblang Kabupaten Cirebon: Kelimpahan dan Keanekaragaman Plankton - Putri Hawa; Fatimatuzzahroh Feti; Nurul Ekawati; Teni Novianti (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
This study aimed to determine the types, abundance, and diversity index of plankton in the Sinyur Jamblang Dam, Warujaya Village, Cirebon Regency. Plankton is an important indicator for assessing the quality and productivity of a body of water. The research method used was an exploratory survey with purposive sampling at three stations: the inlet, the middle of the dam, and the outlet. Plankton samples were collected using a plankton net and observed under a microscope using a Sedgwick-Rafter Counting Cell. The results showed that phytoplankton were dominated by Chlorophyta (77%), and zooplankton were dominated by Zoothamnium (50%). The plankton diversity index (H') was 0.86, which is considered low, indicating the waters have low-moderate productivity. The highest phytoplankton abundance was recorded at 398,000 cells/L and the lowest at 102,000 cells/L. This study revealed that 21 genera of plankton were identified in the Sinyur Jamblang Dam, consisting of 14 genera of phytoplankton and 7 genera of zooplankton. Plankton abundance ranged from 81 to 1,488 individuals/L, with dominance by the class Chlorophyceae. The diversity index (H’) ranged from 1.3 to 1.9, which falls into the moderate category, indicating that the aquatic environment still supports plankton life.